Discover Mars - Skurzynski, Gloria; National Geographic Society (U.S.) (Washington, D.C. : National Geographic Society, 1998)
Reviews results from the study of Mars, from Copernicus through the Viking and Pathfinder missions, and speculates on a future human landing.
"Ages 8 up"--Jacket.
Includes index.
L.A. Recommended Foreign Language.
Wilson's Junior High School.
6.6
3-6
Keywords: Mars (Planet) -- Juvenile literature; Mars (Planet); Mars (Planet)